Antagonists of group I metabotropic glutamate receptors and cortical afterdischarges in immature rats - Lojková-Janecková, Denisa; Ng, Jessica; Mares, Pavel (Epilepsia, 2009)
PURPOSE: Antagonists of group I metabotropic glutamate receptors (mGluRs) are known to exhibit anticonvulsant action without serious side effects. Recently we found anticonvulsant effects of specific antagonists of mGluR subtypes 1 and 5 (AIDA and MTEP) against pentetrazol-induced convulsions in developing rats. In order to determine if the effects of these two antagonists are not exclusively restricted to pentetrazol-induced seizures, we studied their action in a novel seizure model involving immature rats. METHODS: Epileptic afterdischarges were elicited by low-frequency stimulation of sensorimotor cortical region in 12-, 18-, and 25-day-old rats with implanted electrodes. Drugs were administered intraperitoneally after the first afterdischarge: AIDA in doses from 5 to 40 mg/kg; MTEP in doses from 2.5 to 40 mg/kg. The stimulation was then repeated five more times with the same current intensity. Electrocorticographic and motor phenomena were recorded and evaluated. RESULTS: AIDA did not significantly influence movements during stimulation, afterdischarges as well as clonic seizures accompanying afterdischarges. In contrast, MTEP was able to significantly shorten afterdischarges without changes in the two motor phenomena. The effect of MTEP was best expressed in 12-day-old rats; in 25-day-old rats the trials exhibited only a transient shortening of afterdischarges after high doses of MTEP. DISCUSSION: In contrast to similar action against pentetrazol-induced seizures, AIDA and MTEP substantially differ in their action on cortical epileptic afterdischarges. The anticonvulsant action of MTEP in the present model diminishes with age.
Keywords: Anticonvulsants; Epilepsy; Pentylenetetrazole; pohybová aktivita; konvulziva; epilepsie; antikonvulziva; novorozená zvířata; metabotropní glutamátové receptory podtypu 5; Convulsants; Receptors, N-Methyl-D-Aspartate; krysa rodu Rattus; elektroencefalografie; zvířata; pentylentetrazol; mozková kůra; Excitatory Amino Acid Antagonists; Pyridines; potkani Wistar; Cerebral Cortex; receptory N-methyl-D-aspartátu; Animals, Newborn; Rats, Wistar; Male; Receptors, Metabotropic Glutamate; Receptor, Metabotropic Glutamate 5; pyridiny; antagonisté excitačních aminokyselin; Electroencephalography; Rats; receptory metabotropního glutamátu; Motor Activity; Animals; mužské pohlaví